Collaborative and Interinstitutional Networking as a Professional Way of Addressing Education During the COVID-19 Pandemic (Itinerarios Educativos, 2020)
This article presents an experience dealingwith a network developed by trainers of educators inthe field of Natural Sciences working in six Higher Education Institutes in the province of Santa Fe, Argentina,during the period of preventive and mandatory socialisolation due to the Covid-19 pandemic. Suspension ofteaching activities in traditional physical spaces and thesubsequent irruption of the distance education model asan alternative to give continuity to training processes atHigher Education was an event that urged to be faced.The initial confusion gave way to a collective, plural,and cooperative initiative, framed in an interinstitutional research project through collaborative networkingthat prevented us from being trapped by immobility.The work –fully developed by means of digital communication technologies– not only allowed us to buildknowledge about Natural Science teaching practicesdeveloped in primary schools along the first weeks ofthe quarantine, but it also generated a democratic andparticipatory environment in virtual communities. Thisexchange of diverse knowledge, materials, and experiences enriched us at both professional and human level.The present work addresses our effort to systematizethe group experience.
Keywords: Pandemic; natural science teaching; collaborative networking; virtual communities; systematization of experiences